2005
DOI: 10.1111/j.1462-5822.2005.00635.x
|View full text |Cite
|
Sign up to set email alerts
|

Eicosanoid-mediated proinflammatory activity of Pseudomonas aeruginosa ExoU

Abstract: SummaryAs Pseudomonas aeruginosa ExoU possesses two functional blocks of homology to calcium-independent (iPLA 2 ) and cytosolic phospholipase A 2 (cPLA 2 ), we addressed the question whether it would exhibit a proinflammatory activity by enhancing the synthesis of eicosanoids by host organisms. Endothelial cells from the HMEC-1 line infected with the ExoU-producing PA103 strain exhibited a potent release of arachidonic acid (AA) that could be significantly inhibited by methyl arachidonyl fluorophosphonate (MA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
96
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(101 citation statements)
references
References 63 publications
3
96
0
Order By: Relevance
“…A recent study by Saliba et al [35] showed that ExoU modulates the production of eicosonoid mediators by endothelial cells, favoring the inflammatory response associated with P. aeruginosa infection. The present study suggests that ExoU and ExoT may also be directly involved in the induction of COX-2.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study by Saliba et al [35] showed that ExoU modulates the production of eicosonoid mediators by endothelial cells, favoring the inflammatory response associated with P. aeruginosa infection. The present study suggests that ExoU and ExoT may also be directly involved in the induction of COX-2.…”
Section: Discussionmentioning
confidence: 99%
“…M. tuberculosis can also inhibit the formation of the proinflammatory lipid LTB 4 , further shifting the host lipid environment toward an antiinflammatory state (24). P. aeruginosa produces the 15-lipoxygenase LoxA (25,26), as well as the phospholipase ExoU (27), both of which can potentially generate antiinflammatory signals. However, unlike many airway pathogens, P. aeruginosa survives in a hyperinflammatory environment, particularly in the context of chronic lung disease (2).…”
Section: Discussionmentioning
confidence: 99%
“…ExoU is incapable of acting on the extracellular surface because interaction with the intracellular enzyme superoxide dismutase 1 is required for PLA 2 activity (105). In the lung, ExoU is thought to target epithelial cells, endothelial cells, and macrophages (100,117).…”
Section: Bacterial Pla 2 Smentioning
confidence: 99%